Factor related to preterm premature rupture of membrane among pregnant women - Sofiana, Kartika; Wahyuningsih, Heni Puji; Meilani, Niken (Intelektual Pustaka Media Utama, 2024)
The incidence rate of premature rupture of membranes in Yogyakarta, Indonesia was 10.1%, the highest rate in Indonesia. This study's goal was to determine factors related to premature rupture of membranes among pregnant women in Sardjito Hospital. There were 220 pregnant women, 110 in the premature rupture of membranes or case group and 110 no premature rupture of membranes as control group. Urinary tract infection, anemia, and preterm premature rupture of membrane and the characteristics were the research factors. The Chi-square test and logistic regression were used to examine the data. Secondary data from medical records for the period January 2021 December 2022 was taken. Result of this study showed that 49.1% of the pregnant women in the case group had anemia, and 47.3% had urinary tract infections. In the control group had anemia 30.9% of pregnant women, while urinary tract infections infected 61.8% of them. Urinary tract infections and anemia were associated with a greater incidence of preterm premature rupture of membranes, according to a bivariate analysis with p-values of 0.042 and 0.009 (p-value=0.05). Anemia was the most significant factor associated with the incidence of preterm premature rupture of membranes (OR=2.26).